2009
DOI: 10.1039/b909525j
|View full text |Cite
|
Sign up to set email alerts
|

Understanding underlying processes in formic acid fuel cells

Abstract: Obsolescence, defined as the process of declining performance of buildings, is a serious threat for the value, the usefulness and the life span of built properties. Thomsen and van der Flier (2011) developed a model in which obsolescence is categorised on the basis of two distinctions, i.e. between endogenous and exogenous cause-effect relationships and between physical and behavioural cause-effect relationships. In this way, the model presents a classification of underlying factors of obsolescence. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
136
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(137 citation statements)
references
References 97 publications
(163 reference statements)
1
136
0
Order By: Relevance
“…When the two REs located at the equal potential positions in Figure 3 cell impedance spectra (sum of the impedance spectra listed above) were equal to the measured whole cell impedance spectra (simultaneously recorded between the anode and cathode using the 2-electrode method), apart from small discrepancies at high frequencies ( .15 is also consistent with previous studies [20,21] that showed that the sum of the anode and cathode impedance spectra vs. the same RE was equal to the impedance spectrum of the cell.…”
supporting
confidence: 77%
“…When the two REs located at the equal potential positions in Figure 3 cell impedance spectra (sum of the impedance spectra listed above) were equal to the measured whole cell impedance spectra (simultaneously recorded between the anode and cathode using the 2-electrode method), apart from small discrepancies at high frequencies ( .15 is also consistent with previous studies [20,21] that showed that the sum of the anode and cathode impedance spectra vs. the same RE was equal to the impedance spectrum of the cell.…”
supporting
confidence: 77%
“…The electrooxidation of formic acid to carbon dioxide CO 2 on a metal surface is accepted to take place via a dual path mechanism, dehydrogenation and dehydration [17]. In the current model, the direct pathway is assumed to be the dominant oxidation of formic acid as indicate in (1).…”
Section: Mass Transport and Electrochemical Modelmentioning
confidence: 99%
“…It is to note that the electrooxidation of formic acid on Pt and selected Pt-group metal surfaces is a dual pathway mechanism. Adsorbed carbonate monoxide can be produced at the formic acid dehydration pathway which is a poisoning intermediate and can block the dehydrogenation pathway, which is the direct path for generating active intermediate of H + and releasing electrons [16,17]. Since Pt-Ru has a significant increase in the rate of formic acid electrooxidation [16], catalyst ink was prepared using 10 mg/cm 2 of Pt-Ru 20:20 atom wt% alloy (E-TEK) and 1.5 mg/cm 2 of Nafion (5 wt% Nafion 5112, DuPont).…”
Section: Introductionmentioning
confidence: 99%
“…The direct formic acid fuel cell (DFAFC) is a promising power source [1][2][3][4]. Owing to this technological importance, electrooxidation of formic acid (HCOOH) taking place at the anode catalyst in DFAFC has been studied intensively, especially in acidic media.…”
Section: Introductionmentioning
confidence: 99%